Foot Reflexology Improves Intestinal Peristalsis in Postoperative Caesarean Patients - Tri Johan Agus Yuswanto; Eko Adi Putra; Roni Yuliwar (Aloha International Journal of Health Advancement (AIJHA), 2021)
The recovery of intestinal peristalsis in post cesarean section patients shows the recovery of digestive system function after receiving spinal anesthesia, so it should be restored as soon as possible. This study aims to analyze the effect of foot reflexology on increasing intestinal peristalsis in postoperative sectio caesarea patients. This study applied a non-equivalent control group design, involving 30 patients. Data on intestinal peristalsis were collected by auscultation, then analyzed using the Mann-Whitney U test. The mean value of the frequency of intestinal peristalsis in the group that received the intervention in the form of reflexology on the soles of the feet was 3.67 times/minute; while for the control group, the mean frequency of intestinal peristalsis was 1.67 times per minute. The results of the Mann-Whitney U test resulted in a p-value = 0.000. This shows that there was a difference in the frequency of intestinal peristalsis in postoperative cesarean section patients between the intervention group and the control group; So it is concluded that reflexology on the soles of the feet is effective in increasing the frequency of intestinal peristalsis in post-cesarean section patients. Keywords: foot reflexology massage; intestinal peristalsis; post sectio caesarea